Dementia with Lewy bodies: a comparison of clinical diagnosis, FP-CIT single photon emission computed tomography imaging and autopsy. Issue 11 (12th March 2007) - Walker, Zuzana; Jaros, Evelyn; Walker, Rodney W H; Lee, Lean; Costa, Durval C; Livingston, Gill; Ince, Paul G; Perry, Robert; McKeith, Ian; Katona, Cornelius L E
Abstract : Background: Dementia with Lewy bodies (DLB) is a common form of dementia. The presence of Alzheimer's disease (AD) pathology modifies the clinical features of DLB, making it harder to distinguish DLB from AD clinically during life. Clinical diagnostic criteria for DLB applied at presentation can fail to identify up to 50% of cases. Our aim was to determine, in a series of patients with dementia in whom autopsy confirmation of diagnosis was available, whether functional imaging of the nigrostriatal pathway improves the accuracy of diagnosis compared with diagnosis by means of clinical criteria alone. Methods: A single photon emission computed tomography (SPECT) scan was carried out with a dopaminergic presynaptic ligand [ 123 I]-2beta-carbometoxy-3beta-(4-iodophenyl)-N-(3-fluoropropyl) nortropane (FP-CIT; ioflupane) on a group of patients with a clinical diagnosis of DLB or other dementia. An abnormal scan was defined as one in which right and left posterior putamen binding, measured semiquantitatively, was more than 2 SDs below the mean of the controls. Results: Over a 10 year period it was possible to collect 20 patients who had been followed from the time of first assessment and time of scan through to death and subsequent detailed neuropathological autopsy. Eight patients fulfilled neuropathological diagnostic criteria for DLB. Nine patients had AD, mostly with coexisting cerebrovascular disease. Three patients had other diagnoses. The sensitivity of an initial clinical diagnosis of DLB was 75% and specificity was 42%. The sensitivity of the FP-CIT scan for the diagnosis of DLB was 88% and specificity was 100%. Conclusion: FP-CIT SPECT scans substantially enhanced the accuracy of diagnosis of DLB by comparison with clinical criteria alone.